Indication of Mild Hemolytic Reaction Among Preterm Infants With ABO Incompatibility. Issue 6 (3rd February 2016) - Yogev‐Lifshitz, Maya; Leibovitch, Leah; Schushan‐Eisen, Irit; Taran, Camelia; Strauss, Tzipora; Maayan‐Metzger, Ayala
Abstract : Background: Among term infants, ABO incompatibility is a leading cause of hemolytic disease and neonatal jaundice. With respect to preterm infants, data are lacking. Objective: To evaluate the incidence and severity of ABO incompatibility hemolytic disease among preterm infants with respect to hemolytic and jaundice parameters. Design: Clinical and laboratory data were collected retrospectively from the medical records of 118 ABO‐incompatible preterms born at gestational age (GA) 29–34 weeks, as well as 118 controls matched for GA, birth weight, and multiplicity. All infants were born at the Sheba Medical Center Tel‐Hashomer between 2009 and 2012. Results: The study and control groups were similar on all maternal and neonatal outcome parameters. No differences between the groups were recorded throughout hospitalization regarding hematocrit levels or the need for blood transfusion. Bilirubin levels were higher among the study (ABO‐incompatible) group during the first 10 days of life; however, no significant differences were found regarding the need for phototherapy. Upon evaluating subgroups divided by GA, we found no differences on any hematological and jaundice factors among preterms of 29–31 weeks, whereas among preterms of 32–34 weeks higher positive direct antiglobulin test (DAT) results (7% vs. 0% in the control, P = 0.014) as well as higher bilirubin levels were documented. Conclusions: Among ABO‐incompatible preterm infants with GA 29–34 weeks, there is no evidence of significant hemolytic reaction derived from placental transfer of antibodies. With increasing GA, antibody transfer becomes more significant, resulting in more positive DAT results and greater incidence of neonatal jaundice.